Pengaruh Perpanduan Media Statis dan Dinamis Terhadap Pemahaman Konsep Siswa pada Materi Transpor Membran Sel - Yuliani, Dwi Sukmawati; Suranto, Suranto; Ramli, Murni (Universitas Sebelas Maret, 2022)
The dynamics of cell structure and function is an important basic topic for understanding the more complex phenomena of living organisms. Cell-related learning requires means that can interpret the structures and mechanisms that occur in cells. The use of static and dynamic media is expected to increase students' understanding of concepts related to cellular material that cannot be studied directly. This study aims to determine the effect of the combination of static and dynamic media on students' understanding of the concept of cell membrane transport material. The background of the research is the unavailability of fun and interactive learning media for cell membrane transport materials. This study is a Quasi-Experimental design. The applied treatment was the use of a combination of static and dynamic media in the experimental class and the use of static media in the control class. The research was carried out on XI high school students who have studied cell membrane transport material. The instruments of this study were pre-test and post-test forms. The data analysis used is quantitative data analysis using independent t-test based on pre- and post-test scores. The results showed that in the independent t-test the significance value was 0.001; significance < 0.05, there are differences in the results of the concept comprehension tests of the control class and the experimental class, so it can be said that the use of a combination of static and dynamic media affects the students' conceptual understanding. The effectiveness of using a combination of static and dynamic media is 76.03 with an effective category.